Optimization of the Role and Function of the Village Head in Resolving Land Disputes (A Case Study in Tabongo Village, Dulupi District, Boalemo Regency) - Hengki Abubakar; Sastro Mustapa Wantu; Nopiana Mozin (SEAN Institute, 2026)
This research aims to analyze the optimization of the role and function of the Village Head in resolving land disputes in Tabongo Village and to identify the constraints faced in the process. This study employs a qualitative method with a descriptive case study approach to gain an in-depth understanding of the land dispute phenomenon in a natural context. Data collection techniques were conducted through observation, in-depth interviews, and documentation studies involving key informants such as the Village Head, the Village Consultative Body (BPD), community leaders, and the disputing parties. The results indicate that the Village Head's role has been implemented through mediation and deliberation mechanisms, yet it is not yet optimal as it has not been able to provide strong legal certainty and sustainable resolutions. Furthermore, the main constraints identified are the weak land administration and proof of land ownership, as well as a lack of institutional coordination. In conclusion, optimizing the role of the Village Head requires strengthening capacity as a mediator while simultaneously enhancing administrative and legal functions. The implications of this research emphasize the importance of organizing land administration, improving the competence of village officials, and strengthening inter-institutional coordination to achieve effective, fair, and sustainable dispute resolution.